Baile do Carmo: festa, movimento negro e política das identidades negras em Araraquara-SP - Tenório, Valquíria Pereira (2010)
This PhD research examines the construction of identity in an annual celebration, a playful event known as Baile do Carmo, carried out by the black population of Araraquara for over 70 years. It is possible by means of a specific event to discuss the invisibility of this population in local history, including the dynamic process of construction affirmation of black identity. To do this, I analyze how this event took shape over various historical periods and its relations with the Brazilian black movement, showing the changes in the Baile and the nature of its presence in the collective memory of the black population. I also try to understand how the tradition of the Baile do Carmo was (re) created and its role in the fight against discrimination and racism. This party provides a way to discuss relations between black and white people in Araraquara. The examination of these relations was only possible through the collection of oral interviews with participants and non-participants, both black and white, as well as extensive bibliographic study of ethnic and racial themes.